PSYCHOLOGICAL SUPPORT FOR FAMILIES AFFECTED BY WAR (BY THE EXAMPLE OF THE 2020 ARTSAKH WAR) - Mikaelian, Marine (Modern Psychology, 2024)
The article presents work aimed at identifying the psychological problems of families who suffered from the 44-day war in Artsakh, and their post-war social and psychological rehabilitation. Psychological support was provided to 50 families living in different regions of Armenia. The families were classified according to these criteria: families with wounded soldiers, families of war victims, forcibly displaced families. For 6 months, in-person and long-distance psychological support was provided to 130 people. Both individual and group support was provided. The main method of work was a psychotherapeutic conversation. An eclectic approach was applied. Psychological support had 3 main directions, since we dealt with different problems: trauma, loss, displacement. The author’s model of psychological rehabilitation of military personnel, created in 2020 from their own experience of working with the wounded during and after the war, was applied. It consists of 6 stages: desensitization, transition from thoughts to emotions and bodily sensations, activation of resources, anchoring, new history, socio-psychological recovery. The work was performed within the framework of cognitive-behavioral, rational, gestalt, humanistic, existential, logo-, photo- and sedative therapy. Body-oriented, cognitive-behavioral, positive and polyvagal therapies were used to relieve emotional stress, verbalize feelings and strengthen positive thoughts of family members of the wounded. With families of the war victims, the farewell ritual of A.B. Kabikenova "Koshtasu", which includes 6 techniques built on a combination of existential and gestalt therapy: gratitude, asking for forgiveness, resentment, love, farewell, lesson. Work with displaced persons had the following focus - to survive negative life events, overcome the crisis of personal identity, adequately assess their own situation, adapt to a new environment, form psychological stability. In the course of the work, a number of psychological problems of the wounded, their families, families of war victims and displaced persons were revealed. As a result of psychological support, it was possible to face traumatic experience, verbalize and discharge emotions, reflect on their own experiences, mobilize resources, develop skills to manage emotions, rethink life, mitigate the ontological crisis, expand the time perspective, stimulate prospective motivation, activate coping mechanisms, psychologically readapt to the conditions of life, provide post-traumatic personal growth.